Implementation of Obstacle Course Games as a Strategy for Developing Gross Motor Skills in Early Childhood Education at Ar Rahmah PKK Kindergarten - Siva Indana Setyawati; Nur Fatimah; Ivonne Hafidlatil Kiromi (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
The purpose of this study is to describe the use of obstacle courses to stimulate the gross motor skills of 5–6-year-old children at the PKK AR RAHMAH Kindergarten. This study employs a qualitative, descriptive approach to capture and explain field phenomena in greater depth. Data collection techniques included observation, interviews, and documentation. The data analysis process involved phases of data reduction, data presentation, and drawing conclusions, with data validity tested using source and technique triangulation. The research findings confirm that obstacle course games contribute positively to children’s gross motor development, particularly in terms of balance, motor coordination, agility, and physical strength. The majority of children demonstrated significant developmental progress, shifting from the “Beginning to Develop” (BD) category to “Developing as Expected” (BD) and ultimately to “Developing Very Well” (DVW). Furthermore, this activity was shown to stimulate active engagement, learning motivation, and children’s self-confidence through a play-based learning environment. This study contributes to the field of early childhood education, particularly by offering innovative and easily implementable gamebased learning strategies to promote children’s gross motor development. Overall, obstacle course games are an effective learning strategy for optimizing the physical and gross motor development of young children.